Evaluasi Progam Literasi Informasi pada Kegiatan Hari Kunjung Perpustakaan - Vivit Wardah Rufaidah; Herwan Junaidi (Perpustakaan Nasional RI, 2021)
Information literacy program that can be categorized as a training program requires evaluation to show whether the program has been achieved as expected. This study aims to develop a literacy program and determine the effectiveness of the information literacy program on Library Visit Day. The study used a descriptive research method with the research population being all participants of the information literacy program on the 2019 Library Visit Day at the Ministry of Agriculture's PUSTAKA totaling 69 people. Samples were taken from 27 participants in the literacy class for researchers and students, and 42 people in the literacy class for extension workers/farmers/general public. The research method refers to the evaluation of the effectiveness of the training program/training Kirkpatrick (2004). The results of the study show that all of the indicators assessed (level 1-level 4) in the evaluation of the information literacy program carried out by PUSTAKA on Library Visit Day 2019 were considered very satisfactory even though they had not been able to meet the 100% expectations. The improvement strategies needed to improve the information literacy program in the future are: socialization through various media is needed with sufficient time; development of training materials; additional time for the implementation of the literacy program; literacy development programs for students; making a guide for program literacy participants; develop literacy programs directly to extension workers and farmers in the field.